THE IMPACT OF SURFACE AND DEEP EDUCATIONAL UNITS ON DEVELOPING FEMALE STUDENTS’ COGNITIVE ACHIEVEMENT AND ACCURACY OF FLEURET - Asst. Prof. Dr. Muhammad Diaa Abdul Rasul (Galaxy International Interdisciplinary Research Journal, 2024)
The study aimed to prepare educational units according to my deep and superficial method in improving cognitive achievement. As for the population, it included third-year students in the College of Physical Education and Sports Sciences at Al-Muthanna University, who numbered (131). As for the study procedures, the researcher used the experimental method with a pre- and post-test, for its suitability. Nature of the research: The researcher distributed the deep and superficial scale to the control and experimental research groups (46 female students) after excluding (8) from the total number of the exploratory sample. After collecting the results and processing them statistically, the researcher concluded that those with the deep method in the experimental group were the best in the control group.